Investigating the Effectiveness of Mobile Peer Support to Enhance the Quality of Life of Older Adults: A Systematic Literature Review - Saare, Murtaja Ali; Hussain, Azham; Wong, Seng Yue (International Association of Online Engineering (IAOE), 2019)
Aging is the biological, psychological, or social change that occur with the passage of time, which leads to functional impairment, and eventually chronic diseases. The number of people living older is rapidly increasing, and there is a natural decline in physical activity. The reduced mobility affects their daily life activities making them dependent on others for health. Therefore, mobile technologies such as m-health applications provide potential for enhanced health care among older adults. The present study highlights the factors that affect the adoption of smartphone applications, and potential factors such as mobile peer support can facilitate older adults to adopt latest technologies. However, previous studies have remained unsuccessful in explaining the moderating role of mobile peer support. Therefore, this paper aims to provide an insight with potential solution to the challenges of aging life, hence, enhancing their quality of life. This paper is only a conceptual explanation, which aims to identify the possible factors that influence their smartphone adoption using a systematic literature review on relevant peerreviewed papers. It is expected that this work will lead towards the empirical findings on the explanation of the interplay of the peer support to address the relationship of assistive mobile health applications and quality of life. This paper provides directions for future studies in improving the quality of life of older adults by using technology. © 2019 International Association of Online Engineering.